Transtorno do Espectro Autista: um estudo sobre concepções familiares e interações entre irmãos - Lemos, Emellyne Lima de Medeiros Dias (2020)
Autistic Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by a continuum of losses, with different intensities and early manifestation in the socio-communicative domain and through restrictive and repetitive behaviors. Considering these characteristics, the experiences related to them and their influence on development, the role of family contexts and, more specifically, the interactions established between siblings in this process stands out. Substantiating on the bioecological model, it is based on the understanding that multiple factors are related to these contexts, and the coexistence with a family member with ASD can be influenced by a variety of aspects related to the characteristics of people, processes, contexts and time (PPCT). In this direction, this thesis aims to analyze the conceptions about family experiences and the interactions between siblings of families of individuals with ASD. Therefore, five studies were performed. The first presents theoretical and methodological aspects of the bioecological model, articulating them with ASD and fraternal experiences. The results demonstrate the relevance of the model's applicability to the studied phenomenon, as it elucidates positive aspects of development, which can act in these experiences and assist families and professionals. The second study aimed to analyze the conceptions of young people with ASD, their mothers and siblings concerning their family experiences. Interviews were conducted with 12 mothers, 17 siblings of individuals with ASD and two teenagers with ASD, which were transcribed and analyzed using the content analysis technique. According to the results, the respondents used protective factors through their activities, conceptions and support networks, despite the presence of risk factors. The third study aimed to analyze interactions between siblings with typical development and those with ASD, in situations of free play, based on three case studies. The proximal processes were analyzed in terms of interactional episodes and the data triangulation technique was used, due to the different instruments in the research design. The study showed the importance of daily activities for the siblings' development. The inter-influences between the PPCT dimensions were elucidative of the interactions and their duration time was influenced by previous knowledge of activities and objects and by the characteristics of interactions between peers. It stands out that the maternal mediation played a prominent role in this process. The fourth study brings an experience of research feedback through the focus group technique and analyzes the contents that emerged from the speeches of five mothers of young people with ASD. The meeting was recorded and registered in field diaries. The recordings were transcribed, analyzed, discussed and presented in eight categories. The mothers highlighted themes related to ecological transitions such as: the moment of diagnosis, fear of their finitude and preparation of children to this stage, in addition to the need for support, guidance and strategies related to the coexistence with their children. The fifth study deals with the experience of four teenagers, siblings of individuals with ASD, facing research's return from a conversation circle. Data were registered in recordings and field diaries. The recordings were transcribed, analyzed and discussed based on the literature. The teenagers showed interest on the responses of the peers, as it indicates the importance of exchanging experiences. The statements were characterized by empathy, maturity and naturalness in sharing reports. They also reported feeling represented by the survey results and made suggestions to other families. It was found that the strategies used by families and their support networks can favor emotional support and that interactions in these contexts can promote development. It is expected to contribute to the development of new research and interventions in the area.